2018
DOI: 10.3390/su10041212
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners Recycling Attitude and Behaviour in the Australian Construction Industry

Abstract: Construction waste management and recycling is widely discussed. However, at present there is still a significant amount of waste generated during the construction process. Considering this fact, this research aims to analyse the recycling attitudes and behaviours in the Australian construction industry. This paper investigates attitudes and behaviour towards recycling habits in construction; understands how recycling is viewed and carried out by practitioners in the industry; explains the causes of these stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 44 publications
(65 reference statements)
2
21
0
Order By: Relevance
“…It is reported that recycled aggregate can have lower embodied energy in addition to reduced transport emissions, especially where recycled materials are reused in close proximity to the site of re-processing [22]. A study in Japan estimates that a typical residential building constructed of recycled materials would save a minimum of 10% of energy demand [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that recycled aggregate can have lower embodied energy in addition to reduced transport emissions, especially where recycled materials are reused in close proximity to the site of re-processing [22]. A study in Japan estimates that a typical residential building constructed of recycled materials would save a minimum of 10% of energy demand [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is a market that is largely influenced by various stakeholders across the supply chain of waste material [38]. While there is a large body of research on stakeholders' behaviours and attitudes for waste minimisation practices [22,28,[39][40][41][42], there is a little research around stakeholders' perceptions of utilising C&D waste recycled in the construction industry. The overall finding from studies on waste management attitudes and behaviour shows that while industry supports further recycling it is still not widely adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived behavioural control relates to the difficulty or easiness of performing a certain behaviour and it often reflects past experiences (Ajzen, 1991). According to the TPB theory, PBC has a strong influence on behavioural intention or directly on behaviour (Ajzen, 1991;Mamun et al, 2019;Tam et al, 2018). A person's behaviour is not just reliant on their will, but also on other factors such as PBC (Ari & Yilmaz, 2016).…”
Section: Perceived Behavioural Control and Recycling Behaviourmentioning
confidence: 99%
“…Keeping in mind that the participation of residents/waste producers is entirely absent, the maximization of waste resources towards the production of decentralized energy is seriously impeded. Considering also that behavioral patterns and socioeconomic factors influence participation in community-based waste management programs [55,56], incentives and e-tools for a hybrid participatory effort should be put forward to facilitate the middle pathway approach in an e-framework. Assembling the network of nodes of the intelligent WtE supply chain in one ICT platform can be helpful.…”
Section: Example Short Desciption/objectivesmentioning
confidence: 99%